1997
DOI: 10.1046/j.1365-2885.1997.00049.x
|View full text |Cite
|
Sign up to set email alerts
|

Midazolam and ketamine induction before halothane anaesthesia in ponies: cardiorespiratory, endocrine and metabolic changes

Abstract: Six Welsh gelding ponies were premedicated with 0.03 mg/kg of acepromazine intravenously (i.v.) prior to induction of anaesthesia with midazolam at 0.2 mg/kg and ketamine at 2 mg/kg i.v.. Anaesthesia was maintained for 2 h using 1.2% halothane concentration in oxygen. Heart rate, electrocardiograph (ECG), arterial blood pressure, respiratory rate, blood gases, temperature, haematocrit, plasma arginine vasopressin (AVP), dynorphin, beta-endorphin, adrenocorticotropic hormone (ACTH), cortisol, dopamine, noradren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
24
0
2

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 22 publications
0
24
0
2
Order By: Relevance
“…Midazolam has been shown to act synergistically with other induction agents [20] and is reported to reduce the induction dose of propofol in both dogs and cats [21,22]. Reduced respiratory rates associated with midazolam have been previously reported in horses and rabbits [8,25] along with increased post-induction apnoea in horses and goats [26,27], although these are not consistent observations [26,28]. Nishimura et al [23] demonstrated that midazolam has no intrinsic analgesic properties but when co-administered with dexmedetomidine it enhanced analgesia in rats [24].…”
Section: Discussionmentioning
confidence: 99%
“…Midazolam has been shown to act synergistically with other induction agents [20] and is reported to reduce the induction dose of propofol in both dogs and cats [21,22]. Reduced respiratory rates associated with midazolam have been previously reported in horses and rabbits [8,25] along with increased post-induction apnoea in horses and goats [26,27], although these are not consistent observations [26,28]. Nishimura et al [23] demonstrated that midazolam has no intrinsic analgesic properties but when co-administered with dexmedetomidine it enhanced analgesia in rats [24].…”
Section: Discussionmentioning
confidence: 99%
“…We observed minimal cardiovascular changes using MKM-TIVA in horses, such as mild decreases in heart rate, cardiac output and cardiac index and mild increases in stroke volume and systemic vascular resistance. Midazolam produces minimum cardiopulmonary effects [16] and minimal decreases in arterial blood pressure in horses [5,12]. Medetomidine produces decreases in heart rate, cardiac output and increase in systemic vascular resistance by activating central and peripheral α 2 -adrenoceptors [16,27].…”
Section: Discussionmentioning
confidence: 99%
“…The central muscular relaxation produced by guaifenesin can be replaced by benzodiazepines, including diazepam [4], climazolam [1] and midazolam [5,9,12]. Midazolam may be one of the most useful injectable benzodiazepine because it is water-soluble.…”
mentioning
confidence: 99%
“…Cardiopulmonary parameters in the horse change throughout the course of anesthesia, even when the end tidal concentration of volatile agent is kept constant. The degree and exact timing of these changes depends on a number of factors including the pre‐medicant and anesthetic induction agents employed, and whether or not the animal was breathing spontaneously (Luna et al. 1997, Raisis et al.…”
Section: Discussionmentioning
confidence: 99%